Pediatric surgery and self-reported anxiety in children and their parents: A psychometric analysis of the state-trait operation anxiety (STOA) questionnaire - Barkmann, Claus; Härter, Valentina; Trah, Julian; Reinshagen, Konrad (Frontiers in Pediatrics, 2023)
Objective: The preoperative experience in pediatric surgery can cause significant anxiety for both, children and their parents. To date there is no questionnaire available that assesses the child’s self-report or both, the child’s and parent’s self-reported anxiety. The aim of this study was to perform a psychometric analysis of the State-Trait Operation Anxiety (STOA) which provides this option. Methods: The data based on a randomized controlled study conducted with n = 90 child-parent dyads. The psychometric analyses were performed using classical test theory, including item statistics, Cronbach’s α, factor analysis, and test-retest reliability. Results: The statistics of the anxiety items were good overall for both ratings following common guidelines. The item means indicated that the items tended to be rather difficult which reduces the reliability for lower anxiety levels. The given scale structure was confirmed overall for both informants. However, a one-factor structure instead of two factors was found for state anxiety. The internal consistencies and retest reliabilities were good to very good. Follow-up analyses confirmed the sensitivity to change for state anxiety. Child anxiety was hardly correlated with parental anxiety, and age and gender effects were rather small. Conclusions: The STOA questionnaire is the first psychometrically tested questionnaire specifically for fears of surgery that can be used for self-report among children, adolescents, and their parents. Future studies should collect further evidence of its validity as well as comparative scores for specific patient groups and norm values to increase the utility of the instrument.